Investigating Preschool Teacher Candidates' STEM Teaching Intention and the views about STEM Education - Ugras, Mustafa; Genç, Zülfü (My University, 2018)
The objective of the present study was to determine the views of pre-service preschool teachers on Integrated Science Technology Engineering and Mathematics (STEM) education and their tendencies about integrated STEM instruction. The study group included 35 preservice teachers. The present study, conducted as a single group research model with pre-test-post-test experimental method, was completed in 8 weeks. Semi-structured interview form developed by the authors and the \"Integrated STEM Instructional Tendencies Scale\" developed by Lin and Williams (2016) adapted to Turkish by Hacıömeroğlu and Bulut (2016) were used as data collection instruments. The qualitative data obtained are described with the content analysis methodology. The quantitative data were analyzed with paired sample t-test. After the implementation of the STEM education program, it was determined that pre-service preschool teachers had positive views on STEM education approach in general. Furthermore, according to results of the study that STEM education would encourage student to think, transform theoretical knowledge into practice, and to acquire the skills to obtain concrete products using the theoretical knowledge that they acquired in the class. The majority of the participating preservice teachers indicated that undergraduate programs should include science, technology, engineering and mathematics courses, teachers from different fields should collaborate, and the teachers should receive STEM training.
Keywords: Bilgisayar Bilimleri; Yazılım Mühendisliği; Fizik; Uygulamalı; Eğitim; Eğitim Araştırmaları